Hadamard fractional integrals and derivatives with respect to functions (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this article, we study generalized fractional derivatives and integrals that contain kernels a generalized logarithm depending on a positive continuous function increasing. We generalize the Laplace transform in order to be applicable for the generalized fractional integrals and derivatives.
Keywords: Generalized fractional integrals; Generalized Caputo-Hadamard fractional derivative; Generalized Laplace transform.